Peran Policy Entrepreneur dalam Mendorong Kemitraan dan Penguatan Rantai Pasok UMKM di Indonesia - Rossa Novitasari; Qomariyatus Sholihah; Khusnul Prasetyo (Research and Development Agency Ministry of Home Affairs, 2025)
This article aims to explore the role of public officials (politicians and bureaucrats) as policy entrepreneurs in initiating policies that encourage partnerships and strengthening MSME supply chains. This research uses an exploratory qualitative method to understand the phenomenon in depth and formulate the problem in more detail. Data collection was conducted through semi-structured interviews with purposive sampling technique. The results showed that each public official played an important role in each strategy. Framing the problem is done with strong arguments to arouse public awareness, while network expansion is carried out through partnership forums between MSMEs and large companies, business matching, and utilization of international networks. Advocacy coalitions were built with campuses, marketplaces, SMEXcellence program initiation, buyer missions, and Inabuyer B2B2G Expo. Exemplary leadership is reflected in the full support of Kopontren Al-Ittifaq and the protection of imported goods. In an effort to increase the scale of change, policy entrepreneurs initiated the Rumah Produksi Bersama (RPB) and Minyak Makan Merah (M3) to create a sustainable supply chain climate.